Assessment of Quantitative and Allelic MGMT Methylation Patterns as a Prognostic Marker in Glioblastoma. Issue 3 (March 2016) - Kristensen, Lasse S.; Michaelsen, Signe R.; Dyrbye, Henrik; Aslan, Derya; Grunnet, Kirsten; Christensen, Ib J.; Poulsen, Hans S.; Grønbæk, Kirsten; Broholm, Helle
Abstract : Methylation of the O 6 -methylguanine-DNA methyltransferase ( MGMT ) gene is a predictive and prognostic marker in newly diagnosed glioblastoma patients treated with temozolomide but how MGMT methylation should be assessed to ensure optimal detection accuracy is debated. We developed a novel quantitative methylation-specific PCR (qMSP) MGMT assay capable of providing allelic methylation data and analyzed 151 glioblastomas from patients receiving standard of care treatment (Stupp protocol). The samples were also analyzed by immunohistochemistry (IHC), standard bisulfite pyrosequencing, and genotyped for the rs1690252 MGMT promoter single nucleotide polymorphism. Monoallelic methylation was observed more frequently than biallelic methylation, and some cases with monoallelic methylation expressed the MGMT protein whereas others did not. The presence of MGMT methylation was associated with better overall survival (p = 0.006; qMSP and p = 0.002; standard pyrosequencing), and the presence of the protein was associated with worse overall survival (p = 0.009). Combined analyses of qMSP and standard pyrosequencing or IHC identified additional patients who benefited from temozolomide treatment. Finally, low methylation levels were also associated with better overall survival (p = 0.061; qMSP and p = 0.02; standard pyrosequencing). These data support the use of both MGMT methylation and MGMT IHC but not allelic methylation data as prognostic markers in patients with temozolomide-treated glioblastoma.